The influence of dialect upon the perception of dysarthic speech. (July 2014) - Dagenais, Paul A.; Stallworth, Jamequa A.
Abstract The purpose of this study was to determine the influence of dialect upon the perception of dysarthric speech. Speakers and listeners were self-identifying as either Caucasian American or African American. Three speakers were Caucasian American, three were African American. Four speakers had experienced a CVA and were dysarthric. Listeners were age matched and were equally divided for gender. Readers recorded 14 word sentences from the Assessment of Intelligibility of Dysarthric Speech. Listeners provided ratings of intelligibility, comprehensibility, and acceptability. Own-race biases were found for all measures; however, significant findings were found for intelligibility and comprehensibility in that the Caucasian Americans provided significantly higher scores for Caucasian American speakers. Clinical implications are discussed.